(untitled) (Research, Society and Development, 2021)
Among the factors that contribute to childhood obesity are unhealthy eating and lack of physical exercise. The aim of this study was to assess the development of childhood obesity and studies on physical exercise and sports used to combat childhood obesity. This research is a descriptive bibliographic review. Scientific articles available online between 2003 and 2019 were used for the bibliographic survey. The search for articles was performed in the academic Google database and PubMed from August to January 2021. The practice of physical exercise and sports promoted greater energy expenditure, metabolic benefits, heart rate control, improvement in cardiorespiratory function, locomotor skills, laterality, endurance and reduced body mass index in children.